2021
DOI: 10.1093/pubmed/fdab316
|View full text |Cite
|
Sign up to set email alerts
|

Equity of national publicly funded health insurance schemes under the universal health coverage agenda: a systematic review of studies conducted in Africa

Abstract: Background:The implementation of publicly funded health insurance schemes (PFHIS) is the major strategy to drive progress and achievement of universal health coverage (UHC) by 2030. We appraised evidence on the equity of insurance schemes across Africa.Methods: We conducted a systematic review of published studies that assessed equity in health insurance schemes implemented under the UHC agenda in Africa. Six databases, Web of Science, Medline, CINAHL, Scopus, Cochrane Library, EMBASE and World Bank eLibrary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…Results from a 2021 study by Singh and colleagues in India showed that states with higher penetration of PFHIS among richer quintiles have failed to cover disadvantaged populations [ 53 ]. Similar results have been seen in studies in LMICs: PFHIS enrolment often misses disadvantaged populations and is instead covering wealthier quintiles [ 54 , 55 ]. Studies cite lack of awareness and political will as major reasons for low coverage of eligible populations [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 84%
“…Results from a 2021 study by Singh and colleagues in India showed that states with higher penetration of PFHIS among richer quintiles have failed to cover disadvantaged populations [ 53 ]. Similar results have been seen in studies in LMICs: PFHIS enrolment often misses disadvantaged populations and is instead covering wealthier quintiles [ 54 , 55 ]. Studies cite lack of awareness and political will as major reasons for low coverage of eligible populations [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 84%